Pregnancy outcomes after maternal Zika virus infection in a non-endemic region: prospective cohort study. (May 2019) - Rodó, C.; Suy, A.; Sulleiro, E.; Soriano-Arandes, A.; Maiz, N.; García-Ruiz, I.; Arévalo, S.; Rando, A.; Anton, A.; Vázquez Méndez, É.; Garrido, M.; Frick, A.; et al.
Abstract: Objectives: The aim was to describe pregnancy outcomes after Zika virus (ZIKV) infection in a non-endemic region. Methods: According to the Spanish protocol issued after the ZIKV outbreak in Brazil in 2015, all pregnant women who had travelled to high-burden countries were screened for ZIKV. Serological and molecular tests were used to identify ZIKV-infected pregnant women. They were classified as confirmed ZIKV infection when reverse transcription (RT) PCR tested positive, or probable ZIKV infection when ZIKV immunoglobulin M and/or immunoglobulin G and ZIKV plaque reduction neutralization tests were positive. Women found positive using molecular or serological tests were prospectively followed-up with ultrasound scans and neurosonograms on a monthly basis until delivery; magnetic resonance imaging and amniotic fluid testing were performed after signed informed consent. Samples of placenta, and fetal and neonatal tissues were obtained. Results: Seventy-two pregnant women tested positive for ZIKV infection: ten were confirmed by RT-PCR, and 62 were probable cases based on serological tests. The prevalence of adverse perinatal outcomes was 33.3% (three out of nine, 95% CI 12.1–64.6%): two cases of congenital ZIKV syndrome (CZS) and one miscarriage, all born to women infected in the first trimester of gestation. All ZIKV-confirmed women had persistent viraemias beyond 2 weeks (median 61.50 days; IQR 35.50–80.75). Amniotic fluid testing was only positive in the two fetuses with anomalies. Conclusion: The prevalence of perinatal adverse outcomes for women with ZIKV-confirmed infection was 33.3%. Amniocentesis for ZIKV RT-PCR is recommended when fetal abnormalities are found. Intensive prenatal and postnatal follow-up of ZIKV-infected pregnancies is advised in confirmed cases.